Evaluation of critical aspects in clinical and forensic management of sexual violence: A multicentre Ge.F.I. project. (September 2020) - Gino, Sarah; Bo, Marco; Ricciardelli, Rossana; Alù, Milena; Boschi, Ilaria; Carnevali, Eugenia; Fabbri, Matteo; Fattorini, Paolo; Piccinini, Andrea; Previderè, Carlo; Verzeletti, Andrea; Tozzo, Pamela; et al.
Highlights: Competence of healthcare personnel is of fundamental importance in sexual assault. Clinical and forensic examination at the same time. Defining specific pathways and adopting homogeneous procedures. The identification of male biological material is not a problem for laboratory. Typing of genetic profiles is influenced by time elapsed between event and sampling. Abstract: Violence against women is a violation of human rights, crossing all cultures, classes, levels of education, earnings, ethnic and age groups. We conducted a retrospective study to review forensic records of sexual assault examinations carried out in different Italian health facilities and to correlate these findings with the results of the forensic DNA analyses. The goal was to determine which factors could have affected the obtained results, to identify the fundamental aspects to search for while examining a sexual assault victim in order to gather useful evidence to identify the offender and reconstruct the dynamics of the fact. We analysed 102 cases that occurred between 2006 and 2017, coming from ten participating laboratories. Despite a relatively limited number of cases, this study shows that the ability to ascertain the presence of male biological material in the samples collected is not a problem for forensic laboratories and seems to be influenced by other factors, such as how much time elapsed between the event and the sampling, the availability of the aggressor's biological material on the victim and the identification of biological fluids/stains. Therefore, the need for health structures to adopt specific protocols has been highlighted. It is necessary for health structures to define specific pathways and adopt homogeneous procedures or operational protocols, and it is essential to provide adequate training for health personnel. The results of the study could be useful in drafting and revising protocols/guidelines implemented in Italian hospital. Issues related to the limited number of analyses requested by Italian Authorities are also discussed.